Incidence and Risk of Hypertension in Cancer Patients Treated With Atezolizumab and Bevacizumab: A Systematic Review and Meta-Analysis - Jiang, Linhan; Tan, Xiaoxia; Li, Jun; Li, Yaling (Frontiers in Oncology, 2021)
Purpose This study aims to inform previous clinical assessments to better understand the total risk of hypertension with atezolizumab and bevacizumab (hereafter referred to as “A-B”) in cancer patients, and reduce future incidence of hypertension-related cardiovascular complications. Methods Databases, including PubMed, Embase, Cochrane, and Web of Science were searched to identify relevant studies, which were retrieved from inception to March 6, 2021. Studies focused on cancer patients treated with A-B that provided data on hypertension were included. Statistical analyses were conducted to calculate hypertension incidence and relative risk (RR) with a random-effects or fixed-effects model, hinging on heterogeneity status. Results Ten studies including 2106 patients with renal cell carcinoma (RCC), hepatocellular carcinoma (HCC), ovarian cancer, anal cancer, neuroendocrine tumors (NETs), and cervical cancer were selected for this meta-analysis. For patients treated with A-B, the all-grade and high-grade (grade 3) hypertension incidence were 31.1% (95% CI: 25.5-37.3) and 14.1% (95% CI: 10.9-18.1), respectively. No significant difference was observed in all-grade hypertension incidence between RCC and a non-RCC patients (32.9% [95% CI: 25.3-42.6] v.s. 29.2% [95% CI: 19.7-39.6)]). However, the number of high-grade hypertension incidence in RCC patients (9.4% [95% CI: 4.1-21.3]) was lower than that of non-RCC patients (15.6% [95% CI: 12.8-19.1]). RCC or HCC patients who received the A-B treatment were associated with significantly increased risk of all-grade hypertension with a RR of 7.22 (95% CI: 3.3-15.7; p = 0.6) compared with patients treated with atezolizumab. Conclusions Cancer Patients treated with atezolizumab and bevacizumab have a significantly increased risk of hypertension. Sufficient monitoring is highly recommended to prevent the consequences of treatment-induced hypertension and other cardiovascular complications.